The Implementation of Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power in Indonesia, A Comparative Study (Lex Jurnalica, 2004)
Victimology belives that in criminal offenses, the victims are those who mast suffered among all who took part in the offense. In exiting criminal justice system, if there is a criminal offense, ussually both the police, the prosecutor, and the judge pay attention only to the accused. What about the victim? Higjly likely, nobody pys adequate attention to them. The victim must take care of them selves; they have to pay all treatment expenses, medical and all hospital cost including counseling charge and health rehabilitation. The victims who become as witnesses must come to investigation place on tehir own, while the accused are provided with special transportation. In the investigation place the accused is given as separate resting place while the victims and witnesses, sadly, must look after them anywhere else.Key Words: Victim of Crime, Abuse of Power, Victimology